Enhancing Art Literacy through Interactive Teaching Methods in Higher Pedagogical Education - Sa’diyev Soli Tolipovich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores methods to enhance art literacy among students in higher pedagogical education through interactive teaching strategies. It emphasizes the role of project-based learning, flipped classroom techniques, collaborative work, and digital technologies in developing students’ artistic skills, critical thinking, and creative competencies. The study highlights the significance of student-centered approaches in fostering independent learning, aesthetic awareness, and professional readiness.